P115 THE IBD CANDIDATE GENE, PTPN2, RESTRICTS INTESTINAL BARRIER DEFECTS AND CLAUDIN-2 EXPRESSION VIA STAT INHIBITION. (18th January 2018) - Krishnan, Moorthy; Marchelletta, Ronald R; Alvarez, Rocio; McCole, Declan F
Abstract: Introduction: Loss-of-function mutations in the protein tyrosine phosphatase non-receptor type 2 (PTPN2) gene locus increase IBD susceptibility. We reported that PTPN2 knockdown (PTPN2-KD) in intestinal epithelial cells (IECs): (i) increased IFN-g activation of STAT signaling; (ii) reduced IEC barrier function; (iii) increased expression of the tight junction (TJ) protein, claudin-2, by IFN-g; and that the claudin-2 promoter contains a STAT binding sequence. Increased claudin-2 expression occurs in IBD and increases permeability to cations thus reducing transepithelial electrical resistance (TER). Aim: To confirm PTPN2 regulation of barrier function in vivo and identify the mechanisms of STAT regulation of claudin-2 expression. Results: In Ussing chamber studies, TER was significantly reduced in cecum from Ptpn2 knockout (KO) and heterozygous (Het) mice vs. wild-type (WT) littermates indicating increased electrolyte permeability. Immunostaining and western blotting showed progressive increases in claudin-2 expression and STAT-1 phosphorylation (Y701) in Het and KO mice vs. wild-type intestine. Claudin-2 was also elevated in intestinal enteroids from Ptpn2-deficient mice. STAT-1 siRNA significantly decreased the elevated claudin-2 expression in PTPN2-KD IECs. Chromatin immunoprecipitation (ChIP) analysis showed increased STAT-1 binding to the claudin-2 promoter in PTPN2-KD vs. control cells. Claudin-2 promoter-luciferase reporter construct activity was significantly elevated in PTPN2-KD vs. Con-shRNA IEC and was further increased by IFN-g (1000 U/ml). This effect was lost by two different mutations of the STAT binding site thus confirming the requirement of STAT binding for increased claudin-2 transcription in PTPN2-KD IECs. Conclusion: Loss of functional PTPN2 increases susceptibility to inflammation-induced tight junction reorganization, providing an explanation for the association of PTPN2 mutants with UC and CD.